2017
DOI: 10.5312/wjo.v8.i2.87
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of bone tissue engineering in orthopaedic patients

Abstract: Bone defects may impede normal biomechanics and the structural stability of bone as an organ. In many cases, the correction of bone defects requires extensive surgical intervention involving the use of bone-grafting techniques and other procedures in which healing is slow, there is a high risk of infection and considerable pain is provoked - with no guarantee of complete correction of the defect. Therefore, the search for surgical alternatives continues to present a major challenge in orthopaedic traumatology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 106 publications
0
27
0
2
Order By: Relevance
“…Previous research has already shown that hASCs have various differentiation potentials and can differentiate into other cells [ 17 , 32 , 33 ]. Several lines of research have illustrated that stimulating factors are able to promote proliferation and osteogenic differentiation of ASCs [ 34 ]. Thus, we hypothesized that PEMF is likely to enhance hASC proliferation and differentiation into osteoblasts or their progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already shown that hASCs have various differentiation potentials and can differentiate into other cells [ 17 , 32 , 33 ]. Several lines of research have illustrated that stimulating factors are able to promote proliferation and osteogenic differentiation of ASCs [ 34 ]. Thus, we hypothesized that PEMF is likely to enhance hASC proliferation and differentiation into osteoblasts or their progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…More than 4.5 million reconstructive surgical procedures are reported to be executed yearly worldwide in response to the bone injuries [36]. A constant increase in diseases such as osteoporosis, tumors, and osteonecrosis has also been witnessed due to disordered lifestyle responsible for annihilation of bone tissues.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Autograft, the gold standard of bone grafts, is commonly used as a surgical solution to solve large bone defects (Calori, Mazza, Colombo, & Ripamonti, ). Yet, bone grafts contain limitations such as donor‐site morbidity and postoperative pain and infection (Guerado & Caso, ). Bone tissue engineering aims to provide alternative treatments for critical‐sized defects through the combination usage of cells, scaffolds, and signaling molecules (Laurencin, Ashe, Henry, Kan, & Lo, ).…”
Section: Introductionmentioning
confidence: 99%